Leaf functional traits of Daphniphyllum macropodum across different altitudes in Mao’er Mountain in Southern China - Chen, Zhangting; Li, Qiaoyu; Jiang, Zhaokun; Yan, Pengbo; Arif, Muhammad (Frontiers in Forests and Global Change, 2024)
Investigating functional traits among mountain species with differing altitude requirements is integral to effective conservation practices. Our study aims to investigate the structural and chemical characteristics of Daphniphyllum macropodum leaves at three altitudes (1100 m, 1300 m, and 1500 m) across southern China to provide insight into changes in leaf functional traits (LFT) as well as plant adaptations in response to changing environmental conditions. Leaf structural characteristics include leaf thickness (LT), leaf area (LA), specific leaf area (SLA), and leaf tissue density (LD), respectively, while chemical properties include carbon-nitrogen-phosphorus (C:N:P) contents and ratios, such as C/N, C/P, and N/P. Our findings demonstrated the significant effect of altitude on both structural (LT, SLA, LD) and chemical aspects (N, C/N, N/P) of LFT. In particular, leaves at 1100 and 1300 m differed greatly, with 1300 m having lower SLA values than 1100 m. Observable trends included an initial increase followed by a decline as the altitude rose. Notable among them were the LT, LD, N, and N/P values at both locations. Traits at 1300 m were significantly higher than at 1100 m; SLA and C/N values displayed an inverse trend, with their lowest values occurring at 1300 m. Furthermore, this research demonstrated various degrees of variation among LFT, with structural traits exhibiting greater fluctuation than chemical traits. Robust correlations were observed among certain traits, such as LT, LD, and SLA. Furthermore, the interdependency relationships between N and C/N, as well as P and C/P, demonstrated interconnectedness. Redundancy analysis indicated that soil factors, specifically P content, exerted the strongest impact on LFT. At 1100 m, D. macropodum employed acquisition strategies; however, at 1300 m, conservation strategies emerged, showing a shift from acquisition strategies at lower altitudes to conservative strategies at higher ones.